ANALYSIS OF SCHOOL ENVIRONMENTAL PLANNING IN IMPROVING QUALITY SCHOOL ENVIRONMENT - Badrudin, Badrudin; Arpiandi, Zoeji (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
School environment planning is a factor that should be made by every school institution. The educational environment is unorganized and not conducive. This disagreement will result in non- focused teaching activities and an educational environment that should be a comfortable place for the child to become non-conductive. In short, this school has a pre-built structure of houses, but can be a school that remains comfortable and in demand by the community around it. The study aims to analyze school environment planning at SDIT AlMubarokah with a focus on efforts to improve the quality of the school environment. The research method used is a qualitative approach by collecting data through observations, interviews, and analysis of documents related to school environment planning. The results of the analysis showed that SDIT AlMubarokah has implemented various planning of the school environment to improve the quality of the environment. It is proved by the result that pupils have a competitive attitude and enthusiasm to go to school. Besides, the planning of the school environment through the active participation of teachers and also parents during the home. As far as the challenges in trying to improve the quality of the school environment in general can be written are the limitations of the budget, the limitation of the space, must adapt to the student's time, and cultivate a stable competitive spirit. It can be concluded that school environment planning has gone quite well despite the many challenges involved